RESPONSE OF BEET TO PHOSPHORUS RATES IN OXISOL WITH HIGH CONTENT OF THE NUTRIENT - Passos, Danilo Dos Reis Cardoso [UNESP]; Cecílio Filho, Arthur Bernardes [UNESP]; Carlos, Tancredo José [UNESP]; Barbosa, Anne Juciely Vieira (FapUNIFESP (SciELO), 2022)
An experiment was carried out aiming to evaluate the effect of phosphorus rates on beet, in an Oxisol with high phosphorus (P) content, in Jaboticabal city, São Paulo, Brazil. The treatments were arranged in a factorial scheme, in a randomized block experimental design with four replicates. The factors evaluated were P rates (0, 120, 240, 360 and 480 kg ha-1 P2 O5) and cultivar ('Early Wonder' and 'Kestrel'). At 50 days after transplanting the seedlings, foliar nitrogen (N), P, potassium (K) and boron (B) contents were evaluated, and there was no effect of the interaction between factors on foliar nutrient contents. The accumulation of these four nutrients was evaluated at harvest. All evaluated nutrients accumulated to higher levels in ‘Early Wonder’ than in 'Kestrel' both in the shoots and tuberous root. N, P and B accumulated more in the tuberous root whilst K accumulated more in the shoots. P dose did not influence the yield. Therefore, phosphate fertilization is not recommended for beet crop when cultivated in an Oxisol with a high content (88 mg dm-3) of available P.
RESPOSTA DA BETERRABA A DOSES DE FÓSFORO EM LATOSSOLO COM ALTO TEOR DO NUTRIENTE
Keywords: Beta vulgaris; Cultivar; Mineral nutrition; Phosphate fertilization; Phosphorus excess